(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Entertainment as the form of expression has always been an important part of our culture. Various art forms like music, dance, storytelling, drama etc. have been used since time immemorial to keep the people entertained, to give them relief, a break from the routine chores of life. Kings used to various patronize artists and art form. During the later stages of 1880s technology made it possible to capture real moving images, the cinematograph and cinema was born.From a very humble beginning in the year 1896 cinema has come a long way. Today the advent of technology has made it possible to offer variety of contents over the internet .The medium is witnessing newer and newer things on everyday basis with developments in technology. The internet and over the top (OTT) content have greatly changed the creation, distribution and consumption of content.The cinemas have been under the regulatory supervision of the CBFC a body under the Ministry of Information and broadcasting, and the content on the television is under the Cable TV network Regulations, the content on OTT platforms has remained outside the purview of regulation. But in past two years a numbers of cases and petitions were filed in the various courts to bring the services offered by the intermediaries under some form censorship regime. The allegation was mainly to prevent the violent, pornographic, obscene blasphemous contents from being easily available on net. The government has brought in the self-censorship code for the OTT platform. How the code works, How far it addresses the concerns of the stakeholders will decide the future of the OTT platforms in India.The longstanding Cinematograph Bill is still pending in the parliament. How the self-censorship code for the intermediaries and the pending Cinematograph Bill for cinemas address the various issues plaguing the entertainment media industry and conflictingly interests of the various stakeholders needs to be seen. Regulation with minimum possible interference is the way out for future.